Pseudouridine Synthase RsuA Captures an Assembly Intermediate That Is Stabilized by Ribosomal Protein S17 - Kumudie Jayalath; Sean Frisbie; Minhchau To; Sanjaya Abeysirigunawardena (Biomolecules, 2020)
The ribosome is a large ribonucleoprotein complex that synthesizes protein in all living organisms. Ribosome biogenesis is a complex process that requires synchronization of various cellular events, including ribosomal RNA (rRNA) transcription, ribosome assembly, and processing and post-transcriptional modification of rRNA. Ribosome biogenesis is fine-tuned with various assembly factors, possibly including nucleotide modification enzymes. Ribosomal small subunit pseudouridine synthase A (RsuA) pseudouridylates U516 of 16S helix 18. Protein RsuA is a multi-domain protein that contains the N-terminal peripheral domain, which is structurally similar to the ribosomal protein S4. Our study shows RsuA preferably binds and pseudouridylates an assembly intermediate that is stabilized by ribosomal protein S17 over the native-like complex. In addition, the N-terminal domain truncated RsuA showed that the presence of the S4-like domain is important for RsuA substrate recognition.